2020
DOI: 10.1098/rsos.192085
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extinction and counterconditioning procedures on operant evaluative conditioning and intersecting regularity effects

Abstract: One of the most effective methods of influencing what people like and dislike is to expose them to systematic patterns (or ‘regularities’) in the environment, such as the repeated presentation of a single stimulus (mere exposure), two or more stimuli (evaluative conditioning (EC)) or to relationships between stimuli and behaviour (approach/avoidance). Hughes et al . (2016) J. Exp. Psychol. Gen. 145 , 731–754. ( doi:10.1037/xge0000100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Both forms of counterconditioning however were effective at reducing negative evaluative responses when tested in a separate affective priming task (cf. Hughes et al, 2020 ). Keller and Dunsmoor (2020) found that more CS category exemplars were remembered following counterconditioning than extinction and that CC reduced the renewal of conditioned fear, while other studies have produced mixed results of similar aversive-to-appetitive counterconditioning methods on the renewal of fear ( Kang et al, 2018 ; Meulders et al, 2015 ; van Dis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both forms of counterconditioning however were effective at reducing negative evaluative responses when tested in a separate affective priming task (cf. Hughes et al, 2020 ). Keller and Dunsmoor (2020) found that more CS category exemplars were remembered following counterconditioning than extinction and that CC reduced the renewal of conditioned fear, while other studies have produced mixed results of similar aversive-to-appetitive counterconditioning methods on the renewal of fear ( Kang et al, 2018 ; Meulders et al, 2015 ; van Dis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%